INTERVENÇÕES LÚDICAS COM MÃES DE RECÉM-NASCIDOS PRÉ-TERMO HOSPITALIZADOS - Perrone, Rosely Aparecida Prandi (2008)
This research investigates the influence of ludical interventions on the reduction of maternal anxiety in mothers of hospitalized preterm newborns, in a university hospital of grande são paulo. Thirty mothers who had premature births are studied, aging from 16 to 40 years old and up to secondary-level schooling, through evaluative-interventive-evolutive study. It begins with a semidirected psychological interview, with the objective of drawing the gestational record, followed by the application of the irritability-depression-anxiety scale IDA, aiming to identify the level of maternal anxiety, and the neonatal perception inventory IPN-I, to verify the expectation of the mothers in relation to the crying, eating and vomit behavior of their preterm babies. After this, ludical interventions are made in 16 meetings, once a week, during 60 minutes, according to the piagetian model, that stimulates affective-emotional and cognitive processes. The data related to the gestational record show that 75% are in the second pregnancy and have already had a miscarriage or fetal death; they have an average gestational age of 31 weeks; average baby´s birth weight of 1,640 kg and average time of hospitalization of 39.93 days. In the analysis of the IDA relating to the anxiety, 75% show a score of high intensity (11.25), also high in relation to the depression (10); the average score (3.73) of the exteriorized irritability is the same of the interiorized irritability (3.23). The correlation between depression and anxiety indicates that an emotional reaction follows the other, and there´s no significant important difference between them (p=0.306). The IPN-I proves that the 30 mothers have compatible expectations of their babies with the babies in general, showing average scores of 8.63 and 9.20 respectively, confirmed by the score 10.0 showed in 75% of the sample, what shows a high expectation in the aspects of sleeping, eating and vomit of the babies. The qualitative analysis reveals that the creation of ludical groups is favorable, with a great joint and motivation of the mothers, favoring the reduction of the anxiety, the adaptation to the reality lived, and the interaction between mother and baby in a healthy way during the hospitalization. The study presents the interventive trajectory of three emblematic cases of different levels of anxiety, ilustrating this evolution. These data suggest that this type of intervention is characterized as a measure of prevention, promotion and preservation of the physical and psychical health of the mother and the premature newborn, with repercussions in the family and in the society.(AU)